Elaboración y aplicación de talleres motivacionales para erradicar el maltrato entre alumnos "bullying" mejorando así el rendimiento académico de los estudiantes de los octavos años del Istituto Tecnológico superior Aloasi, en el año lectivo 2012-2013 - Guaygua Guaigua, Silvia Gabriela (2015)
This investigation made in the “Instituto Tecnológico Superior Aloasí” during the period between 2012-2013; in which participated all of scholar community, taking into account that abuse between students "Bullying" affects the academic performance of students in the teaching - learning, the purpose of the research in this thesis. It was necessary to make activities which help to develop motivational workshops with the students of eighth years of basic education. The important in this investigation is motivated to know, awareness and make a dynamic alternative to counter the bullying in the institution